Pemanfaatan Benda-Benda Kongkret untuk Meningkatkan Hasil Belajar Matematika tentang Pengukuran Panjang dengan Satuan Tidak Baku pada Siswa Kelas 1B Sekolah Dasar Negeri Sambibulu Kecamatan Taman - Fenti Rizqi Auliyah; Delia Indrawati; Siti Elijah Chotimah (Departement of Mathematics Education, 2023)
Utulization of visual aids with concrete objects to improve mathematics learning outcome about measuring length with non standard nits in Class Students 1B SDN Sambibulu semester 2 of the 2022/2023 academic year. This study aims to determine whether teaching aids with concerte objects can improve student learning outcomes class 1 semester 2 of the 2022/2023 academic year in Sambibulu Elementary School, Kecamatan Taman, Kabupaten Sidoarjo. A total of 20 students. In mathematics about measuring length with concrete objects props. Data analysis used quantitative descriptive analysis techniques with the mean, highest score, lowest score presented in tabular form and then described based on the data that had been analyzed and conclusions drawn. The results of this study indicate that through the use of visual aids concrete objects can improve the learning outcomes of class 1B students in learning mathematics about measuring lenght with non-standard units. It can be seen that the average value of the average value of the cycle wich reached 60,34 increased to 83.10 in cycle 2.